To begin the world anew : - Bailyn, Bernard (Knopf, 2003)
With these character sketches of key figures of the American Revolution and illuminating probes of its circumstances, Bernard Bailyn reveals the ambiguities, complexities, and uncertainties of the founding generation as well as their achievements